Raised levels of F2-isoprostanes and prostaglandin F2α in different rheumatic diseases. Issue 6 (1st June 2001) - Basu, S; Whiteman, M; Mattey, D L; Halliwell, B
Abstract : OBJECTIVE: To evaluate oxidative injury and inflammatory status in various rheumatic diseases by measuring the levels of isoprostanes and prostaglandins in serum and synovial fluid. METHODS: The concentrations of 8-iso-PGF2α (F2 -isoprostane indicating oxidative injury) and 15-keto-dihydro-PGF2α (a major metabolite of prostaglandin F2α ) were measured in both serum and synovial fluid aspirated from 26 patients with various arthritic diseases, including rheumatoid arthritis (RA), reactive arthritis (ReA), psoriatic arthritis (PsA), and osteoarthritis (OA). These prostaglandin derivatives were also measured in serum samples collected from 42 healthy control subjects. RESULTS: Overall, serum levels of 8-iso-PGF2α and 15-keto-dihydro-PGF2α were much higher in patients with arthritic diseases than in the healthy control subjects. The levels of 8-iso-PGF2α and 15-keto-dihydro-PGF2α in synovial fluid aspirated from knee joints were also high and varied among various types of arthritic patients. Although the synovial fluid level of these prostaglandin derivatives was sometimes higher than in the corresponding serum sample, this was not a consistent finding. Overall, there was no correlation between serum and synovial fluid levels of 8-iso-PGF2α, or between serum and synovial fluid levels of 15-keto-dihydro-PGF2α . However, a strong relation was found between the levels of 8-iso-PGF2α and 15-keto-dihydro-PGF2α, in both serum ( r s =0.53, p<0.001) and synovial fluid ( r s =0.62, p<0.001). CONCLUSIONS: These data suggest that both free radical mediated oxidative injury and cyclo-oxygenase dependent inflammatory responses are closely correlated in various types of arthritis.